Thermal Studies of Lithium-Ion Cells: Ensuring Safe and Efficient Energy Storage - Beata Kurc; Xymena Gross; Ewelina Rudnicka; Łukasz Rymaniak (Energies, 2024)
This work investigated the impact of temperature on the diffusion of lithium ions within cells. To achieve this, electrochemical impedance spectroscopy (EIS) analysis was conducted at various temperatures across three distinct cells. These cells utilized an electrode composed of corn starch meringue and were paired with three different electrolytes. Notably, one electrolyte included an additional 5% of starch. The objective of this study extends beyond merely determining resistance from graphical representations; it also entails performing a kinetic analysis of specific systems, with a particular emphasis on elucidating the significance of the lithium-ion diffusion coefficient as a critical parameter. The cell with 1 M LiPF6 in the EC/DMC/DEC electrolyte and corn starch-based electrode exhibited the most horizontally oriented Warburg curve, representing the smallest angle.